ADAM10 mediates the house dust mite‐induced release of chemokine ligand CCL20 by airway epithelium. Issue 12 (11th September 2015) - Post, S.; Rozeveld, D.; Jonker, M. R; Bischoff, R.; van Oosterhout, A. J.; Heijink, I. H.
Abstract: Background: House dust mite (HDM) acts on the airway epithelium to induce airway inflammation in asthma. We previously showed that the ability of HDM to induce allergic sensitization in mice is related to airway epithelial CCL20 secretion. Objective: As a disintegrin and metalloprotease (ADAM)s have been implicated in chemokine shedding, we sought to determine their involvement in HDM‐induced release of chemokines, including CCL20, by airway epithelial cells. Methods: We studied the effects of pharmacological ADAM inhibitors as well as ADAM10 and ADAM17 siRNA downregulation on chemokine release using (multiplex) ELISA in supernatants from HDM‐exposed human bronchial epithelial 16HBE cells and primary normal human bronchial epithelial cells (NHBE) at 4–24 h. Results: House dust) mite markedly increased CCL20 levels in both 16HBE and NHBE cells (16–24 h). In 16HBE cells, the HDM‐induced increase was observed as early as 4 h upon exposure and the use of specific inhibitors indicated the involvement of ADAM10/17‐mediated shedding. siRNA knockdown of ADAM10, but not of ADAM17, significantly reduced the HDM‐induced release of CCL20 in both 16HBE and NHBE cells. A similar effect was observed for HDM‐induced CCL2, CCL5, and CXCL8 release in NHBE cells. The HDM‐induced increase in CCL20 levels was not affected by protein synthesis inhibitor cycloheximide nor protein transport inhibitor monensin, indicating that HDM induces surface shedding of chemokines. Conclusion: Our data show for the first time that ADAM10 activity contributes to HDM‐induced shedding of chemokines, including CCL20. The ADAM10/CCL20 axis may be a target for novel therapeutic strategies in asthma.